2016
DOI: 10.1371/journal.pone.0161915
|View full text |Cite
|
Sign up to set email alerts
|

Spheroid Formation of Hepatocarcinoma Cells in Microwells: Experiments and Monte Carlo Simulations

Abstract: The formation of spherical aggregates during the growth of cell population has long been observed under various conditions. We observed the formation of such aggregates during proliferation of Huh-7.5 cells, a human hepatocarcinoma cell line, in a microfabricated low-adhesion microwell system (SpheroFilm; formed of mass-producible silicone elastomer) on the length scales up to 500 μm. The cell proliferation was also tracked with immunofluorescence staining of F-actin and cell proliferation marker Ki-67. Meanwh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 38 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…We also showed that spheroids from the microwells have larger populations of cells with stem cell-like properties compared with spheroids formed by conventional tumor spheroid culture methods. The microwell-based spheroid culture method provides the following advantages over the hanging drop method and the other developed spheroid culture platforms: an extended culture period of 1030 days due to easy medium changes; ready for co-culture without direct cell-to-cell contact [30]; easy generation of size-controlled cell spheroids; easy growth medium changes in the device due to the shear-free and stress-free structure [31]; ready application to various cell types; and unlimited throughput, given that 361 cell spheroids can be obtained from a single device. Moreover, the microwell mimics the in vivo environment and contains CSC-secreted factors [32].…”
Section: Resultsmentioning
confidence: 99%
“…We also showed that spheroids from the microwells have larger populations of cells with stem cell-like properties compared with spheroids formed by conventional tumor spheroid culture methods. The microwell-based spheroid culture method provides the following advantages over the hanging drop method and the other developed spheroid culture platforms: an extended culture period of 1030 days due to easy medium changes; ready for co-culture without direct cell-to-cell contact [30]; easy generation of size-controlled cell spheroids; easy growth medium changes in the device due to the shear-free and stress-free structure [31]; ready application to various cell types; and unlimited throughput, given that 361 cell spheroids can be obtained from a single device. Moreover, the microwell mimics the in vivo environment and contains CSC-secreted factors [32].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, choosing PS as the microwell substrate is favorable from a biologist’s perspective because PS is the most commonly utilized plastic for in vitro cell culture research. Compared to PDMS [ 28 ] or polyester [ 13 ] microwells, PS is hassle-free for the researchers in terms of the material accessibility, and more amenable in terms of compatibility with different forms of conventional culture plasticwares, such as Petri dishes [ 3 ] or microtiter plates [ 16 ]. In addition, the PS microwell displayed a gentle concave bottom, and curved microwell structures have been reported to promote the aggregation of spheroids [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the hanging drop method, this microwell system enables the changing of the media during incubation. For cell-cell communication, interspheroid interaction is available via paracrine signaling through the media 109 . A rotating wall vessel can be used to induce polarity or to apply fluidic shear stress to the cell spheroid 110 - 112 .…”
Section: Biomimetic Platforms That Replicate the Physiology Of The Tmmentioning
confidence: 99%